2020
DOI: 10.1055/s-0040-1713597
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Psychosocial Morbidity in Anorectal Malformation and Hirschsprung's Disease

Abstract: Anorectal malformation (ARM) and Hirschsprung's disease (HD) are the most common congenital colorectal anomalies. Despite advances in surgical techniques and improvements in postoperative clinical care, short- and long-term physical and psychosocial morbidity of these patients remains high. This review outlines the current literature on the physical and psychosocial aspects of health-related quality of life (HrQoL) and its confounders in patients with ARM/HD. Moreover, important coping strategies are summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…ARM patients are at long-term risk for impaired health-related quality of life (HrQoL) in both physical and psychosocial aspects [ 4 , 5 ]. Thus, surgical treatment and care for ARM need to be constantly improved by scientific studies and high-quality publications.…”
Section: Introductionmentioning
confidence: 99%
“…ARM patients are at long-term risk for impaired health-related quality of life (HrQoL) in both physical and psychosocial aspects [ 4 , 5 ]. Thus, surgical treatment and care for ARM need to be constantly improved by scientific studies and high-quality publications.…”
Section: Introductionmentioning
confidence: 99%
“…With the more frequent use of laparoscopy for treating high forms of ARM, different studies have not found substantial differences in HrQoL [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with high ARM or associated malformations do not have a reduced HrQoL, probably due to a different mechanism to adjust a new reality in function to accommodate the limitations of their diagnosis, which allows them to control their organic disease, resulting in a higher HrQoL [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…HD patients suffer from a congenital segmental aganglionosis leading to insufficient peristalsis. The standard surgical procedure for HD is resection of the aganglionotic bowel segment via different types of “pull-through operations” [ 24 ]. Despite successful surgical correction of the malformation, patients with ARM and HD regularly continue to face motility and continence issues that persist into adolescence and adulthood ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients struggle with constipation (22–87%) and/or stool incontinence and soiling (17–77%) [ 25 ]. While urinary continence and sexual function in HD are most often impaired due to iatrogenic injury, in ARM patients these factors are mostly determined by severity of the disease which may include a hypoplastic pelvic floor or sacral agenesis [ 24 ]. Additionally, ARM patients frequently suffer from concomitant anomalies which are often VACTERL-associated [ 24 ].…”
Section: Introductionmentioning
confidence: 99%